Evaluation of Complications and Management of Chronic Suppurative Otitis Media: A Retrospective Study - Mehwish Haqdad, Ali Akber Aftab, Ashok Kumar, Sheikh Sajjad Ali, Deepak Rai, Naveed Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate multiple clinical complications and management of chronic suppurative otitis media Study design: A retrospective study Place and Duration: This study was conducted at Jinnah Post Graduate Medical Centre Karachi Pakistan from June 2020 to June 2021. Methodology All patients of chronic suppurative otitis media with intra or extra cranial complications who were admitted to the ENT Department were included in this study. Clinical data, related complications, care, and follow-up were all analyzed. In all patients, pure tone audiometry was used to assess their hearing. Every patient had a high-resolution computer tomography (HRCT) temporal bone scan and all other relevant investigations including aural pus swab for culture and sensitivity done . Every patient with CSOM-related intracranial problems had a Magnetic Resonance Imaging (MRI) brain scan. Results: During the trial of 280 individuals, 42 patients with CSOM complications were observed. A total of 19 of them had intracranial complications, while 23 had extra cranial complications. The youngest patient was five years old, while the oldest was 58 years. The majority of the cases were observed in 11 to 20 years age groups. Only 6 of the 42 individuals had bilateral CSOM, whereas the remaining 36 had unilateral CSOM. Conclusions: CSOM-related problems are still widespread, despite the availability of broad spectrum antibiotics. Patients should be given higher doses of intravenous antibiotics (that breach the blood-brain barrier) followed by mastoid surgery. Early detection of concomitant intracranial complications using HRCT and MRI and adequate antibiotic treatment, abscess drainage, and mastoid surgery as soon as possible are all essential to prevent mortality from CSOM complications.